Principles need to Guarantee When Building Sanctions in Sanctioning Administrative Violations in Vietnam - Loc, Nguyen Xuan; Hien, Phan Trung (VNU Journal of Science: Legal Studies; Vol 36 No 1, 2020)
Along with administrative sanctions, sanctions against administrative violations are determined very early in Vietnam [1] and gradually improved. However, a part of the sanctions is not really comprehensive due to the simple and convenient factor when applied. Under these conditions, important principles stemming from the philosophy of sanctions are not properly addressed. As a result, the application of sanctions faces many difficulties, some of which are incompatible with the nature of the violations or the form of sanctions that are not really consistent with the nature and extent of the acts violate. This does not only affects the consistency in the application of sanctions when sanctioning administrative violations but also sometimes negatively affects the deterrence, validity and effectiveness of sanctioning decisions. Based on the logical thinking, characteristics and characteristics of each type of sanctions, the paper focuses on analyzing the principles to be guaranteed to build a complete administrative sanctions system in Vietnam today. Keywords: Principles in state management, principles in building sanctions, sanctions against administrative violations. References: [1] Regulations on penalties for violations were issued in accordance with Decree No. 143 / CP of May 27, 1977 of the Government Council. [2] Phan Trung Hien: Theory of state and law (vol. 2), National Political Publishing House, Hanoi, 2011 (second edition). [3] Report No. 09 / BC-BTP dated January 8, 2018 of the Ministry of Justice summarizing the implementation of the Law on handling of administrative violations. [4] Clause 1 Article 3 of the Law on handling of administrative violations in 2012. [5] Traffic Newspaper: "The countries that punish people who drank alcohol and beer drive the most strictly" The Ministry of Transport website: http://mt.gov.vn/vn/tin-tuc/64226 /nhung-nuoc-xu-phat-nguoi-uong-ruou--bia-lai-xe-nghiem-khac-nhat.aspx[accessed: 19/3/2020]. [6] Clause 1 Article 23 and Clause 1 Article 52 of the Law on handling of administrative violations 2012. [7] See the following Reports: [8] Report No. 403/BC-BTP dated December 30, 2016 of the Ministry of Justice on law enforcement on handling of administrative violations in 2016. [9] Report No. 28/BC-BTP dated January 23, 2018 of the Ministry of Justice on the implementation of the law on handling of administrative violations in 2017. [10] The Ministry of Justice's Report No. 82/BC-BTP dated March 22, 2019 on the implementation of the law on handling of administrative violations in 2018. [11] On March 18, 2019, Thanh Xuan District Police applied Point a, Clause 1, Article 5 of Decree 16/2013/ ND-CP dated November 12, 2013 of the Government to sanction violations against the Government. D.M.H (31 years old, born in Hai Phong) about gesture, cruel words, provocation, teasing, insulting the honor and dignity of others to punish a man who has committed sexual acts The girl in the lift of the Golden Palm apartment building (Nhan Chinh ward, Thanh Xuan district) https://thanhnien.vn/thoi-su/co-gai-bi-sam-so-trong-thang-may-phat-hanh-chinh-yeu-rau-xanh-200000-dong-1061885.html (accessed September 19, 2019). [12] Viet Khue - Tung Nguyen, Redeeming 100 USD is fined 90 USD: What is the law but not reasonable? https://dantri.com.vn/ban-doc/doi-100-usd-bi-phat-90-trieu-dong-dung-luat-nhung-khong-hop-ly-o-diem-nao-20181109082508651.html [accessed September 19, 2019]. [13] Viet Khue - Tung Nguyen, cited documents. [14] Le Van Thinh: Is the container on the ground a construction ?, Electronic Newspaper of the Ministry of Construction, http://www.baoxaydung.com.vn/news/vn/hoi-_-dap /container-dat-tren-mat-dat-co-phai-la-cong-trinh-xay-dung.html [accessed September 19, 2019]. [15] See the following Reports: Report No. 403 / BC-BTP dated December 30, 2016; Report No. 28 / BC-BTP dated January 23, 2018; Report No. 82 / BC-BTP dated March 22, 2019 of the Ministry of Justice on the implementation of laws on handling of administrative violations in 2016, 2017 and 2018.